Quantified secularism? Counting religious conflicts in French state schools since the 1980s - Ferhat, Ismaïl (British Journal of religious education, 2022)
Religious matters have traditionally been considered as a sensitive subject in French state schools. Since 1989 and the first ‘Muslim headscarf affair’, faith-related conflicts in those institutions have been the subject of a relatively opaque counting policy. Mobilising several state institutions- which alternatively cooperate or compete- this quantification has deeply reshaped the way the French state perceived religious expressions, especially those linked to Islam, in schools. This article, based on newly released archives, uses an interdisciplinary approach (history, education science, political sociology) to study these political and administrative phenomena.